The use of Douyin and beauty self satisfaction among emerging female adults in Malaysia - Foo, Yee Zen (2023)
This study aimed to investigate The Use of Douyin And Beauty Self-Satisfaction Among Emerging Female Adults in Malaysia. Employing a qualitative approach, semi-structured indepth interviews has been conducted with 25 participants selected through a non-probability purposive sampling method. The practical implications of this research were significant for government agencies and organizations seeking to comprehend the psychological behaviors of these audiences shaped by social media consumption. The findings can serve as a valuable reference for the development of tactical and strategic actions, such as campaigns or policies, aimed at fostering a healthy norm and mindset regarding beauty standards among Malaysian youth. The value of this study lies in offering a deeper understanding of the behavioral changes, perspectives, and effects on youth who engage with Douyin in relation to beauty standards.